INFLUENCE OF CAREER OPPORTUNITIES, ORGANIZATIONAL CULTURE, AND THE WORK ENVIRONMENT TURNOVER INTENTION ON PT. RAILINK MEDAN - Annisa Maharani; Nazaruddin; Yeni Absah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This research is motivated by the high level of turnover intention of PT. Railink Medan. Therefore researchers interested in examining whether there is an influence of career opportunity factors, organizational culture and work environment. This research uses quantitative descriptive methods. Obtaining research data is done by distributing questionnaires to all permanent employees in the field of customer service outside of the position of Manager at PT. Railink Medan. The results showed that; (1) the effect of career opportunities on turnover intention is negative and significant; (2) the influence of organizational culture on turnover intention is negative and significant; (3) there is no negative and significant influence of work environment variables on the variable turnover intention at PT. Railink Medan. Therefore, in terms of minimizing the level of turnover intention in PT. Railink Medan so that companies increase opportunities for employees to obtain career opportunities so that employee loyalty is formed to keep working and not leave and look for other jobs outside the company and create a better organizational culture as norms and guidelines to be followed and obeyed by employes.